Human Calmodulin-Like Protein CALML3: A Novel Marker for Normal Oral Squamous Mucosa That Is Downregulated in Malignant Transformation. (8th July 2013) - Brooks, Michael D.; Bennett, Richard D.; Weaver, Amy L.; Sebo, Thomas J.; Eckert, Steven E.; Strehler, Emanuel E.; Carr, Alan B.
Abstract : Oral cancer is often diagnosed only at advanced stages due to a lack of reliable disease markers. The purpose of this study was to determine if the epithelial-specific human calmodulin-like protein (CALML3) could be used as marker for the various phases of oral tumor progression. Immunohistochemical analysis using an affinity-purified CALML3 antibody was performed on biopsy-confirmed oral tissue samples representing these phases. A total of 90 tissue specimens were derived from 52 patients. Each specimen was analyzed in the superficial and basal mucosal cell layers for overall staining and staining of cellular subcompartments. CALML3 was strongly expressed in benign oral mucosal cells with downregulation of expression as squamous cells progress to invasive carcinoma. Based on the Cochran-Armitage test for trend, expression in the nucleus and at the cytoplasmic membrane significantly decreased with increasing disease severity. Chi-square test showed that benign tissue specimens had significantly more expression compared to dysplasia/CIS and invasive specimens. Dysplasia/CIS tissue had significantly more expression than invasive tissue. We conclude that CALML3 is expressed in benign oral mucosal cells with a statistically significant trend in downregulation as tumorigenesis occurs. CALML3 may thus be a sensitive new marker for oral cancer screening.